(untitled) (Journal of Hama University, 2021)
The goal of compensating for lost teeth is to restore oral function and improve masticatory efficiency, which is one of the important criteria for the success of complete dentures. to compare the masticatory efficiency in edentulous patients with conventional mandibular complete dentures and with that of mandibular complete dentures having lingual flanges constructed with flexible acrylic resin. The study sample included 10 completely edentulous patients. Each patient received one maxillary complete denture and two mandibular complete dentures. One mandibular denture was made of conventional heat‑cured acrylic resin (Traditional) and the other had its lingual flanges made of flexible acrylic resin Versacryl. Masticatory effeciency was evaluated using color-changeable chewing gum after two months of treatment with the conventional complete dentures (T1) and after two months of treatment with the conventional maxillary complete denture and mandibular complete denture with lingual flanges made of flexible acrylic resin Versacryl (T2). The statistical analysis showed that The masticatory effeciency of mandibular complete dentures with flexible lingual flanges was significantly greater than conventional mandibular complete dentures (P= 0.004). The use of flexible acrylic resin lingual flanges in the construction of mandibular complete dentures improved masticatory efficiency in edentulous patients.